Descriptive analysis of long COVID sequelae identified in a multidisciplinary clinic serving hospitalised and non-hospitalised patients. Issue 3 (2nd August 2021) - Johnsen, Stine; Sattler, Stefan M.; Miskowiak, Kamilla Woznica; Kunalan, Keerthana; Victor, Alan; Pedersen, Lars; Andreassen, Helle Frost; Jørgensen, Barbara Jolanta; Heebøll, Hanne; Andersen, Michael Brun; Marner, Lisbeth; Hædersdal, Carsten; et al.
Background: There are emerging data of long-term effects of coronavirus disease 2019 (COVID-19) comprising a diversity of symptoms. The aim of this study was to systematically describe and measure pulmonary and extra-pulmonary post-COVID-19 complications in relation to acute COVID-19 severity. Methods: Patients attending a standard of care 3 months post-hospitalisation follow-up visit and those referred by their general practitioner because of persistent post-COVID-19 symptoms were included. Patients underwent symptomatic, quality of life, pulmonary (lung function and high-resolution computed tomography (HRCT)), cardiac (high-resolution ECG), physical (1-min sit and stand test (1-MSTST), handgrip strength, cardiopulmonary exercise testing (CPET)) and cognitive evaluations. Results: All 34 hospitalised and 22 out of 23 non-hospitalised patients had ≥1 complaint or abnormal finding at follow-up. Overall, 67% of patients were symptomatic (Medical Research Council (MRC) ≥2 or COPD assessment test (CAT) ≥10), with no difference between hospitalised versus non-hospitalised patients. Pulmonary function (forced expiratory volume in 1 s (FEV1 ) or diffusing capacity of the lung for carbon monoxide ( D LCO )) <80% of predicted) was impaired in 68% of patients. D LCO was significantly lower in those hospitalised compared to non-hospitalised (70.1±18.0 versus 80.2±11.2% predicted, p=0.02). Overall, 53% had an abnormal HRCT (predominantly ground-glass opacities) with higher composite computed tomography (CT) scores in hospitalised versus non-hospitalised patients (2.3 (0.1–4.8) and 0.0 (0.0–0.3), p<0.001). 1-MSTST was below the 25th percentile in almost half of patients, but no signs of cardiac dysfunction were found. Cognitive impairments were present in 59–66% of hospitalised and 31–44% of non-hospitalised patients (p=0.08). Conclusion: Three months after COVID-19 infection, patients were still symptomatic and demonstrated objective respiratory, functional, radiological and cognitive abnormalities, which were more prominent in hospitalised patients. Our study underlines the importance of multidimensional management strategies in these patients. 3 months post-COVID-19, most patients have at least one organ function impairment. All patients have some degree of cognitive impairment and abnormal dyspnoea symptom scores. Abnormal HRCT and impaired D LCO are predominately found in inpatients. #longCOVID https://bit.ly/2QB2j0J